DNA Methylation Aberrant in Atherosclerosis - Dai, Yao; Chen, Danian; Xu, Tingting (Frontiers in Pharmacology, 2022)
Atherosclerosis（AS）is a pathological process involving lipid oxidation, immune system activation and endothelial dysfunction. The activated immune system could lead to inflammation and oxidative stress. Risk factors like aging and hyperhomocysteinemia also promote progression of AS. Epigenetic modifications including DNA methylation, histone modification, non-coding RNA are involved in the modulation of genes between environment and AS formation. DNA methylation is one of the most important epigenetic mechanism in the pathogenesis of AS. However, the relationship between the progression of AS and DNA methylation is not completely understood. This review will discuss the abnormal changes of DNA methylation in AS, including Genome-Wide hypermethylation dominating in AS with an increase of age, hypermethylation links with methyl supply and generating hyperhomocysteinemia, and the influence of oxidative stress with the demethylation process by interfering with the hydroxyl-methylation of TET proteins. The review will also summarize the current status of epigenetic treatment, which may provide a new direction and potential therapeutic targets for AS.